Explanation:
![\large\underline{\sf{Given \:Question - }}](https://img.qammunity.org/2022/formulas/mathematics/high-school/av9bf7hkj5adho5tl42ubeziq5bxrfu4vo.png)
![\sf \: tan\theta = (m)/(n), \: prove \: that \: (msin\theta - ncos\theta)/(msin\theta + ncos\theta) = \frac{ {m}^(2) - {n}^(2) }{ {m}^(2) + {n}^(2) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/istl0gnsn6fy4i7vwybbbftqwoeybbg3pr.png)
![\green{\large\underline{\sf{Solution-}}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/urnur5b0g5pe47mikqhzfz20wdv2bscx5b.png)
Given that
![\red{\rm :\longmapsto\:tan\theta = (m)/(n) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/tew4ntu745g6f6yzsm1gubkuo2facs0r5v.png)
Now, Consider
![\rm :\longmapsto\:(msin\theta - ncos\theta)/(msin\theta + ncos\theta)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9r7hbby1rxacm3efgxpeej2tarntdhuzix.png)
![\rm \: = \: (cos\theta\bigg[m(sin\theta)/(cos\theta) - n\bigg])/(cos\theta\bigg[m(sin\theta)/(cos\theta) + n\bigg])](https://img.qammunity.org/2022/formulas/mathematics/high-school/uokj92q32lkxbe3z95gvzo91a3auaatqkd.png)
![\rm \: = \: (mtan\theta - n)/(mtan\theta + n)](https://img.qammunity.org/2022/formulas/mathematics/high-school/1oqzntda8dpv1gsozvvy8uctxhvhu8vg9b.png)
![\rm \: = \: (m * (m)/(n) - n)/(m * (m)/(n) + n)](https://img.qammunity.org/2022/formulas/mathematics/high-school/q7pwa7jbmcx3o3b6hh4e8qw7y0mb4jvr3l.png)
![\rm \: = \: \frac{\frac{ {m}^(2) }{n} - n}{\frac{ {m}^(2) }{n} + n}](https://img.qammunity.org/2022/formulas/mathematics/high-school/vhza9w8aplu5z65tmcfsfwwfk3f6r11q99.png)
![\rm \: = \: \frac{\frac{ {m}^(2) - {n}^(2) }{n}}{\frac{ {m}^(2) + {n}^(2) }{n}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/z2khmbso3imynyhsxacw5whbpkuqhpi734.png)
![\rm \: = \: \frac{ {m}^(2) - {n}^(2) }{ {m}^(2) + {n}^(2) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/hn25vyuozcej70uu7k1mkxly0br6hv9jk5.png)
Hence,
![\red{\sf \: tan\theta = (m)/(n), \: \rm \implies\: \: (msin\theta - ncos\theta)/(msin\theta + ncos\theta) = \frac{ {m}^(2) - {n}^(2) }{ {m}^(2) + {n}^(2) }}](https://img.qammunity.org/2022/formulas/mathematics/high-school/lf41iy2u9t5tmf4i3mdpja9wsbsatp2vi3.png)
▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬
Additional Information:-
Relationship between sides and T ratios
sin θ = Opposite Side/Hypotenuse
cos θ = Adjacent Side/Hypotenuse
tan θ = Opposite Side/Adjacent Side
sec θ = Hypotenuse/Adjacent Side
cosec θ = Hypotenuse/Opposite Side
cot θ = Adjacent Side/Opposite Side
Reciprocal Identities
cosec θ = 1/sin θ
sec θ = 1/cos θ
cot θ = 1/tan θ
sin θ = 1/cosec θ
cos θ = 1/sec θ
tan θ = 1/cot θ
Co-function Identities
sin (90°−x) = cos x
cos (90°−x) = sin x
tan (90°−x) = cot x
cot (90°−x) = tan x
sec (90°−x) = cosec x
cosec (90°−x) = sec x
Fundamental Trigonometric Identities
sin²θ + cos²θ = 1
sec²θ - tan²θ = 1
cosec²θ - cot²θ = 1